ANALISIS MORFOLOGI JAMBU METE (Anacardium occidentale L.) BERDASARKAN KARAKTER VEGETATIF DI TIGA KABUPATEN SULAWESI TENGGARA - NAWIR, NAWIR; BOER, DIRVAMENA; LAREKENG, SITI HALIMAH; SUAIB, SUAIB; HADINI, HAMIRUL; HISEIN, WAODE SITI ANIMA; ARSYAD, MIRZA ARSIATY (Jurnal Agroteknos, 2022)
Cashew is a promising plant in Southeast Sulawesi due to its reasonably high economic value. This species has been cultivated for years in Southeast Sulawesi, particularly in South Konawe, Konawe, and East Kolaka, with 20 to 30-years-old average plant age. This research aimed to identify morphological variations at the vegetative stage of the cashew in three evaluated Southeast Sulawesi populations (South Konawe, Konawe, and East Kolaka). The descriptive observations were carried out on the leaf apex shape, leaf shape, leaf margin, leaf venation, the color of young and mature leaves, branching pattern, tree habit, ease of peeling bark from the twig, leaf texture, as well as leaf aroma. We indicated the morphological variations in the evaluated cashew. The variations were observed in leaf shape (obovate, oblong, and circular), leaf apex shape (pointed, rounded, and indented), leaf venation (curved up, curved down, and flat), branching pattern (intensive and extensive), tree habit (upright and open, upright and compact, spreading), ease of peeling bark from twigs (difficult and easy), leaf texture (smooth and rough), and aroma (mango-like and guava-like).